2021
DOI: 10.1111/tpj.15210
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a high‐activity diacylglycerol acetyltransferase results in enhanced synthesis of acetyl‐TAG in camelina seed oil

Abstract: Acetyl-triacylglycerols (acetyl-TAG) contain an acetate group in the sn-3 position instead of the long-chain fatty acid present in regular triacylglycerol (TAG). The acetate group confers unique physical properties such as reduced viscosity and a lower freezing point to acetyl-TAG, providing advantages for use as emulsifiers, lubricants, and 'drop-in' biofuels. Previously, the synthesis of acetyl-TAG in the seeds of the oilseed crop camelina (Camelina sativa) was achieved through the heterologous expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Heterologous expression of EaDAcT resulted in accumulation of 40% and 52% of acTAG in seeds of Arabidopsis and Camelina, respectively ( Durrett et al., 2010 ). EfDAcT, functioning more efficiently than EaDAcT, produced an average of 72% acTAG in transgenic Camelina seeds ( Alkotami et al., 2021 ). Interestingly, co-expression of CnLPAT from MCFA-containing coconut and EaDAcT from acTAG-enriched E. alatus in camelina plants expressing UcFATB1 produced acTAGs with MCFAs, which have yet to be found in nature, suggesting a potential synthetic-biology strategy for creating novel lipid structures in plants ( Bansal et al., 2018 ).…”
Section: Section II Optimizing Lipid Accumulation By Channeling Selec...mentioning
confidence: 99%
“…Heterologous expression of EaDAcT resulted in accumulation of 40% and 52% of acTAG in seeds of Arabidopsis and Camelina, respectively ( Durrett et al., 2010 ). EfDAcT, functioning more efficiently than EaDAcT, produced an average of 72% acTAG in transgenic Camelina seeds ( Alkotami et al., 2021 ). Interestingly, co-expression of CnLPAT from MCFA-containing coconut and EaDAcT from acTAG-enriched E. alatus in camelina plants expressing UcFATB1 produced acTAGs with MCFAs, which have yet to be found in nature, suggesting a potential synthetic-biology strategy for creating novel lipid structures in plants ( Bansal et al., 2018 ).…”
Section: Section II Optimizing Lipid Accumulation By Channeling Selec...mentioning
confidence: 99%
“…Beyond this activity, EaDAcT can also acetylate fatty alcohols in vitro ( Bansal and Durrett, 2016 ). Heterologous expression of this enzyme in Arabidopsis yielded 40% of acTAGs in its oil, showing an attractive application of DAcT in the formation process of low viscosity oils for the production of biofuels ( Durrett et al , 2010 ; Liu et al, 2015 ; Tran et al, 2017a ); however, no homologous DAcT was identified and characterized for oilseed crops, or plants with relevant oil in industry applications ( Alkotami et al, 2021 ; Mihálik et al, 2020 ; Tran et al , 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of EaDAcT into the emerging oil seed crop Camelina sativa resulted in acetyl‐TAG levels of about 65 mol% in the best transgenic lines. Combining EaDAcT expression with the RNAi‐mediated suppression of the endogenous camelina DGAT1 enzymes which synthesize lcTAG and thus compete with EaDAcT, resulted in acetyl‐TAG levels as high as 81 mol% (Alkotami et al, 2021; Liu et al, 2015). Higher levels of acetyl‐TAG were subsequently achieved by expressing EfDAcT, a higher activity acetyltransferase enzyme isolated from E. fortunei (Tran, Shelton, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%